Understanding the service provider perspective towards better service quality in local authorities - Yusoff, Wan Zahari Wan; Ismail, Maziah; Ali, Azlan Shah (Emerald, 2010)
Purpose – The paper aims to provide better understanding of internal customer perspectives, i.e. the employees of local authorities (LAs) as a service provider in Malaysia. The research attempts to identify the contributing and the constraining factors affecting the quality of the services to the public. Design/methodology/approach – The paper employs a qualitative approach of primary data collection. Data were obtained through semi-structured interviews and open-ended question interviews. The study conducted involved service providers and officials from Johor Bahru City Council in the capital of Johor state, Malaysia. Findings – The paper revealed that substantial measures should be taken to ensure that the service provider is able to provide better service quality in the delivery system. It was also found that before the service providers are able to offer quality services to the public, the service providers have to first overcome the problems they face. Originality/value – The paper suggests that it is equally important to understand internal customer satisfaction in advance before the authors expect the service providers to offer better service delivery processes to the service receiver's, i.e. external customers in LAs. © 2010, © Emerald Group Publishing Limited.